2020
DOI: 10.3389/fimmu.2020.00638
|View full text |Cite
|
Sign up to set email alerts
|

A Treg-Selective IL-2 Mutein Prevents the Formation of Factor VIII Inhibitors in Hemophilia Mice Treated With Factor VIII Gene Therapy

Abstract: AC designed and performed the experiments, analyzed the results, and wrote and edited the manuscript. XC and CL performed the experiments. LK and MG designed, screened, and provided the Fc.Mut24. MG assisted in the experimental design and edited the manuscript. CM conceived the experiments, supervised the project, and wrote and edited the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In parallel, mouse IL-2 muteins with enhanced Treg selectivity and in vivo half-life, expanded highly suppressive Tregs in tissues ( 298 ) and controlled autoimmunity in the mouse NOD T1D model ( 299 ). Moreover, the IL-2 mutein prevented antibody response to FVIII in a mouse model of hemophilia A ( 300 ), further supporting that Tregs responding to an attenuated IL-2 mutein exert immune suppressive effects. Another class of IL-2 muteins with enhanced affinity to CD25 has also been described, although the activity and selectivity profile of such muteins need to be further evaluated ( 294 ).…”
Section: Il2-mediated Therapymentioning
confidence: 86%
“…In parallel, mouse IL-2 muteins with enhanced Treg selectivity and in vivo half-life, expanded highly suppressive Tregs in tissues ( 298 ) and controlled autoimmunity in the mouse NOD T1D model ( 299 ). Moreover, the IL-2 mutein prevented antibody response to FVIII in a mouse model of hemophilia A ( 300 ), further supporting that Tregs responding to an attenuated IL-2 mutein exert immune suppressive effects. Another class of IL-2 muteins with enhanced affinity to CD25 has also been described, although the activity and selectivity profile of such muteins need to be further evaluated ( 294 ).…”
Section: Il2-mediated Therapymentioning
confidence: 86%
“…We and others have hypothesized that blocking CD25 would favor the accumulation of bioactive IL-2 and a subsequent increase in Treg cells that, in turn, would downregulate the inflammatory reaction ( Nihei et al., 2014 ; Huss et al., 2015 ). So, the game played by IL-2 and Tregs would be very sensitive to possible therapeutic manipulations by increasing or decreasing the availability of IL-2 in many different ways ( Boyman et al., 2006 ; Arenas-Ramirez et al., 2015 ; Chen et al., 2020 ; Khoryati et al., 2020 ; Solomon et al., 2020 ). Therefore, we hypothesized that blocking IL-2 during the initial phases of T. cruzi infection would also cause modifications in the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also demonstrated that Treg enrichment before FVIII challenge was more effective than concomitant treatment (24). Leveraging the same system, we recently reported that combining a Treg-selective Fc-fused IL-2 mutein with FVIII gene therapy also established durable suppression of FVIII Ab formation (25,26).…”
Section: Introductionmentioning
confidence: 86%